PENGARUH KUALITAS LAYANAN, KUALITAS PRODUK DAN PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN PADA PT. NUSANTARA SAKTI DEMAK - Uci Paramita, 13.05.51.0032; Wuryan, Sophiyanto (Students Journal of Economic and Management, 2017)
This purpose of this study was to analysis theeffect of service quality,quality product and perceived price to customer satisfaction PT.NusantaraSaktiDemak.Thepopulation in this study werecustomers who made a purchase on PT.NusantaraSaktiDemak.The number of samples studied were as many as 100 people wereselected as respondents used purposive sampling technique.Data collection methods used in this study wasquestionnaire filled out by respondents. The analysis technique has been done by using validity test, reliability test, linnear regression test,model feasibility test and hypothesis significancetest.Data processing using SPSS Version 19th. The results of this studyshowed that the service quality, product quality and perceived price have positive effect and significant to customer satisfaction. Keywords: Service Quality, Product Quality, Perceived Price and Customer Satisfaction